Manekin Pintar Sebagai Alat Peraga Anatomi Manusia Untuk Anak Penyandang Tunanetra Dan Tunagrahita Berbasis Arduino - Zihan Ika Priana; Amelia Megananda; Muhammad Rizky; Desi Kurniasih; Indica Yona Okyranida (UNIVERSITAS INDRAPRASTA PGRI, 2021)
Science (Natural Science) learning is obtained from the elementary level to the college level, so students need early planting to understand the subjects. IPA material that is very close to daily life such as organs. This material is very important to students because it relates to one's own body. Learning media serves as a medium of help and learning resources for students that aims to facilitate the teaching and learning process. Nowadays, many learning media are utilizing technology. The use of learning media for children with special needs is very important, so that they can receive and understand the materials delivered by teachers. The purpose of this research is to make smart mannequins as human anatomy props for students with visual impairment and arduino-based visual impairment. This research mannequin can function properly and will be conducted expert test tools and use tests to know the effectiveness of the tool in the success of the tool to know the success rate in learning for students